On the research of family relationships - Aramavičiūtė , V. (Psichologija, 1972)
The psychologists state that family relationships influence the development of personality. In order to rest this hypothesis the impact of relationships in morally disadvantaged families on students was tested. Family conditions were tested using questionnaire, interview and essays. The main sources of information were students themselves. The analysis revealed: 1. The important factors that influence child development were relationships between mother and father, parents (especially, mother) and children, and level of confidence (especially, in mother). 2. Abnormal relationships in morally disadvantaged families has effect on the emotional and will disorders in children; children in disadvantaged families are more aggressive with others and are not persistent enough while working in comparison to children from morally normal families.